Ontological model of the process of intensification of teachers’ competencies - Bazarova, Madina; Alibekkyzy, Karlygash; Adikanova, Saltanat; Bugubayeva, Alina; Zhomartkyzy, Gulnaz; Jaxalykova, Akmaral; Baidildina, Aizhan; Keribayeva, Talshyn (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Currently, there is a need to improve the education system and develop interdisciplinary research at all levels of education, from school to postgraduate education. The introduction of interdisciplinary connections contributes to the formation of a holistic understanding of natural phenomena and the connections between them. Thus, this knowledge becomes more meaningful and applicable in practice. This article proposes a conceptual model of the content of education in the form of a thesaurus and ontology. The use of these models will allow you to adaptively select and systematize educational information. The article also discusses the possibilities and experience of using ontological modeling and engineering for the conceptual description of school and higher education. In addition, the article discusses the development of an ontological model of the process of expanding teachers’ competencies with the integration of science, technology, engineering and mathematics (STEM) education. The use of ontological engineering methods will improve the quality of teacher education through the semantic description of knowledge in the subject area and the use of interdisciplinary and STEM approaches in the educational process.